Do We Need Plant Food Supplements? A Critical Examination of Quality, Safety, Efficacy, and Necessity for a New Regulatory Framework - Abdel-Tawab, Mona (Planta Medica, 2018)
Given the expanding market of plant food supplements (PFSs) not undergoing any pre-marketing authorization, the overall quality, safety and efficacy of PFSs were subjected to a critical examination. Although many high-quality PFSs exist on the legal market, quality concerns are in general justified. Besides economic adulteration, active ingredients dramatically differing from label claims and among products were reported in several studies. In addition, PFSs sold via the Internet may be intentionally adulterated with undeclared prescription drugs. Compared to PFSs with only one single herb, PFSs containing herbal mixtures were more involved in moderate and severe clinical courses. Although prohibited by regulation, misleading labels on PFSs are common. Above all, only vague evidence for the efficacy of PFSs exists. Notwithstanding the unproven efficacy and insufficient safety assessment, PFSs represent a relevant source for consumers to get access to herbal preparations in the United States and meanwhile also in Europe, as launching of licensed/registered European herbal medicinal products (HMPs) has steadily decreased. However, being non-vitamin, non-mineral products, PFSs are neither food nor drugs. In terms of protecting public health and providing the consumer with high-quality, effective, and safe PFSs, possibilities are shown how to deal with the many challenges of PFSs. Last but not least, suggestions are made for assigning PFSs a separate regulatory category being less regulated compared to HMPs but more strictly regulated compared to food laws including implementation of good manufacturing practices and a scientific pre-marketing review process by an expert commission.
Keywords: plant food supplements; botanical dietary supplements; herbal products; quality; safety; efficacy